Pengaruh Model Pembelajaran Tipe STAD Terhadap Hasil Belajar IPA SMP PAB 10 Medan Estate - Adlini, Miza Nina; Badres, Shofi Azzahra; Armiati, Rika; Hasibuan, Nadya Wahyuni; Wahdania, Dea (MODELING: Jurnal Program Studi PGMI, 2023)
A teacher, especially a science subject teacher at SMP PAB 10 Medan Estate, is required to choose and use a variety of appropriate learning methods or strategies to help improve student learning outcomes. One of the efforts that can be made to improve biology learning outcomes and meet biology goals is to apply an appropriate learning model. In this study using quantitative research methods where in this study we conducted experiments on 2 classes of SMP PAB 10 Medan Estate. The conventional method of sampling technique used in this study is a random technique sampling where the population has an equal opportunity to become the research sample. The selection of this sample was carried out by drawing lots of three classes with the same major to take two classes that would be used as research samples (random class in parallel class). This research was conducted in class IX at SMP PAB 10 Medam Estate, academic year 2022/2023. The number of samples in this study were 64 students. This sample is divided into 2 classes where the first class is an experimental class which is taught using the STAD type cooperative learning method and the second group is a control class which is taught by the lecture method which only asks students to pay attention to the material provided by the teacher.